Conditional mutations in SERCA, the Sarco-endoplasmic reticulum Ca(2+)-ATPase, alter heart rate and rhythmicity in Drosophila. - Sanyal, S.; Jennings, T.; Dowse, H.; Ramaswami, M. (Journal of comparative physiology. B, Biochemical, systemic, and environmental physiology, 2006)
To analyze the role of cytosolic calcium in regulating heart beat frequency and rhythm, we studied conditional mutations in Drosophila Sarco-endoplasmic reticulum Ca2+-ATPase, believed to be predominantly responsible for sequestering free cytosolic calcium. Abnormalities in the amount or structure of the SERCA protein have been linked to cardiac malfunction in mammals. Drosophila SERCA protein (dSERCA) is highly enriched in Drosophila larval heart with a distinct membrane distribution of SERCA at cardiac Z-lines, suggesting evolutionarily conserved zones for calcium uptake into the sarcoplasmic reticulum. Heart beat frequency is strikingly reduced in mutant animals following dSERCA inactivation, (achieved by a brief exposure of these conditional mutants to non-permissive temperature). Cardiac contractions also show abnormal rhythmicity and electrophysiological recordings from the heart muscle reveal dramatic alterations in electrical activity. Overall, these studies underscore the utility of the Drosophila heart to model SERCA dysfunction dependent cardiac disorders and constitute an initial step towards developing Drosophila as a viable genetic model system to study conserved molecular determinants of cardiac physiology.